2012
DOI: 10.1371/journal.pone.0036655
|View full text |Cite|
|
Sign up to set email alerts
|

GSK-3 Activity Is Critical for the Orientation of the Cortical Microtubules and the Dorsoventral Axis Determination in Zebrafish Embryos

Abstract: The formation of dorsal-ventral (D–V) axis is the earliest event that breaks the radial symmetry and determines the bilateral body plan of a vertebrate embryo, however, the maternal control of this process is not fully understood. Here, we discovered a new dorsalizing window of acute lithium treatment, which covers only less than 10 minutes after fertilization. Lithium treatment in this window was not able to reverse the ventralized phenotype in tokkeabi (tkk) mutant embryos, and its dorsalizing activity on wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…D: Control showing the expression of gsc mRNA in cells of the embryonic shield (es) using the Thisse and Thisse () protocol. Differences between the quality of the in situ hybridizations shown in C and D are confirmed when we compare our results with those obtained by others with a similar method in the same embryonic material (see Shao et al, ). E: Expression of brul mRNA in the lens (arrowhead).…”
Section: To 9‐day‐old Sectioned Embryossupporting
confidence: 82%
See 1 more Smart Citation
“…D: Control showing the expression of gsc mRNA in cells of the embryonic shield (es) using the Thisse and Thisse () protocol. Differences between the quality of the in situ hybridizations shown in C and D are confirmed when we compare our results with those obtained by others with a similar method in the same embryonic material (see Shao et al, ). E: Expression of brul mRNA in the lens (arrowhead).…”
Section: To 9‐day‐old Sectioned Embryossupporting
confidence: 82%
“…Similar gastrulae, that we stained for gsc mRNA using a conventional procedure (Thisse and Thisse, 2008), revealed poorer cell preservation and less precise localization of the hybridization signal (compare Figs. 10C and D) (see also Shao et al, 2012).…”
Section: Zygote and Embryomentioning
confidence: 90%
“…Indeed, a recent study has shown that Sfrp1 and Frzb are two maternal Wnt inhibitors that limit the spatial context of Wnt proteins in dorsal cells (3). In addition, embryos treated with inhibitors that inactivate GSK3 (required for ␤-catenin degradation) from the 32-cell stage to the sphere stage also result in dorsalized phenotypes (14), indicating that GSK3 activity is promoted in ventral cells to ensure ventral cell fate. It is unclear, however, how GSK3 activity in ventral cells is controlled during early embryogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In vertebrates, two genes encode GSK3 (GSK3␣ and GSK3␤) and Axin (Axin1 and Axin2). GSK3␤ is known to be involved in axis formation (14), whereas Axin2 is a direct target of Wnt/␤-catenin signaling and acts as a feedback negative regulator for the same pathway (15). In zebrafish, two genes code for ␤-catenin.…”
mentioning
confidence: 99%
“…The dorsal determinants (DDs) model suggests an intimate relationship between animal-vegetal polarity and the DV axis, because dorsalising signals are enriched in the vegetal pole of the oocyte. Triggered by fertilisation and controlled by microtubules, DDs are asymmetrically transported, from vegetal pole to the prospective dorsal side in zebrafish (Abrams and Mullins, 2009;Mei et al, 2009;Nojima et al, 2010;Langdon and Mullins, 2011;Shao et al, 2012;Tran et al, 2012;Ge et al, 2014) and in Xenopus (Cuykendall and Houston, 2009;Slack, 2014;Carron and Shi, 2016). Several candidate DDs, including Dishevelled, GBP, and Wnt11 in Xenopus (Miller et al, 1999;Weaver et al, 2003;Tao et al, 2005), and Wnt8a in zebrafish (Lu et al, 2011), were thought to be required for dorsal axis formation.…”
Section: Introductionmentioning
confidence: 99%